ANALYSIS OF TOURIST ATTRACTION ON TOURIST VISITING INTEREST IN PERLANG TOURISM VILLAGE CENTRAL BANGKA - Janice Fellicia Japri; Dewanta Facrureza (ZILLZELL MEDIA PRIMA, 2024)
This research is motivated by the growing development of Indonesian tourism, one of which is a tourist village. Tourism villages are cultural diversity to tourist destinations owned by each region. The existence of interesting things contained in the tourist village makes tourists interested in visiting Perlang Tourism Village. In this study, it was found that Perlang Tourism Village was included in the top 50 best tourism villages nominated by ADWI and third place in the digital and creative categories. Therefore, the purpose of this study is to provide input to managers on what attractiveness can be developed to become an advantage for Perlang Tourism Village. This research is entitled